The communicative dynamics and its relation with the social dynamics. Reflections for communication research from the paradigm of critical epistemology - Vivian Romeu (Technium Social Sciences Journal, 2021)
In this work the communicative phenomenon is understood as the germ of social action. This invites us to think of communication as expressive behavior through which the social, even the historical, is configured. Consequently, to think of communication in the social as social action demands to conceive and study the social reality as a reality in constant movement, that is, giving in the given. From the critique of the traditional concept of communication, through the epistemological legacy of Hugo Zemelman, this paper proposes a reflection on the role of communication in the shaping movement of social reality.